Toward Efficiency Limits of Crystalline Silicon Solar Cells: Recent Progress in High‐Efficiency Silicon Heterojunction Solar Cells (Adv. Energy Mater. 23/2022). Issue 23 (16th June 2022) - Sun, Zhaoqing; Chen, Xiaoqing; He, Yongcai; Li, Jingjie; Wang, Jianqiang; Yan, Hui; Zhang, Yongzhe
Abstract : Solar Cells In article number 2200015, Yongzhe Zhang and co‐workers discuss various aspects of silicon heterojunction solar cell (SHJ) research. These solar cells have attracted increasing attention because of their high conversion efficiency and good temperature coefficients. These temperature coefficients are essential in hot and sunny climates, which gives SHJ solar plants great potential to be widely constructed in desert areas.